In vitro and in vivo androgen regulation of Dendropanax morbiferus leaf extract on late-onset hypogonadism - Jung, Myung-A; Oh, Kyo-nyeo; Choi, Eun Jin; Oh, Dool-Ri; Kim, Yu jin; Bae, Donghyuck; Hong, Ji Ae; Pan, SangO; Kim, Ki man; Kim, Dong-Wook; Choi, Chul-yung (Cellular and Molecular Biology, 2018)
Late-onset hypogonadism (LOH) is associated with advancing age and is caused by a deficiency in serum testosterone levels. The aim of this study was to examine the effect of a Dendropanax morbiferus H.Lév. leaf extract (DME) on LOH using TM3 cells and aging male rats as in vitro and in vivo models, respectively. The in vitro effects of DME on testosterone levels and 3Î²-hydroxysteroid dehydrogenase (3Î²-HSD) protein expression in TM3 cells were analyzed. In the in vivo experiments, DME was orally administered to rats at three doses (50, 100, and 200 mg/kg/day) for 4 weeks. DME significantly increased the testosterone levels and 3Î²-HSD protein expression in TM3 cells. The DME groups showed significantly increased levels of androgenic hormones such as testosterone and dehydroepiandrosterone sulfate. The sex hormone-binding globulin production was significantly lower in the DME groups than that in the control group, while the neurohormone levels in the hypothalamic–pituitary–gonadal axis markedly increased. No significant differences were observed in the glutamic pyruvic transaminase, glutamic oxaloacetic transaminase, and prostate-specific antigen levels among the DME and control groups. The triglyceride and low-density lipoprotein cholesterol levels were significantly lower, while the high-density lipoprotein cholesterol levels were significantly higher in the DME groups than those in the control group. The latency time in the rotarod, treadmill, and swimming tests increased with the DME treatment. Furthermore, the sperm counts in the epididymis markedly increased. These results suggest that DME can be effectively used to alleviate the symptoms of LOH.